Genipin-crosslinked gelatin scaffold in tissue engineering: a systematic review - Muhammad Mior Amirul A; Mohd Heikal Mohd Yunus; MH Busra F (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
Gelatin has been frequently used in tissue engineering scaffold due to its favorable biological properties in wound healing enhancement. Genipin, a natural compound derived from Gardenia plants, was shown to be effective in improving physicochemical characteristics of the gelatin scaffold. This systematic review reported the utility of genipin as a crosslinker in gelatin scaffold fabrication. Two electronic databases, namely Scopus and MEDLINE via Ebcoshost were searched for publication between January 1999 and December 2018, using the keywords ‘gelatin’ and ‘genipin’. Articles published in English, reporting the utility of genipin in the fabrication of gelatin sponge were included. The keywords search yielded 830 articles, in which 14 articles were selected and examined in this review. The result of the search provided input in terms of the optimum concentration, crosslinking temperature, and fabrication method of genipin to be used. From the literature, it was found that 0.5% is the optimum genipin concentration and 25˚C is the optimum crosslinking temperature. The result also revealed a gap in the knowledge regarding genipin crosslinker and justifies the need to create awareness of the utility of genipin as a gelatin scaffold crosslinker. The current review provides an extensive overview on the current knowledge on genipin crosslinking and be a guide to an optimal fabrication of the genipin-crosslinked gelatin scaffold.